Technologically mediated human resource management in the gig economy. Issue 19 (28th October 2021) - McDonnell, Anthony; Carbery, Ronan; Burgess, John; Sherman, Ultan
Abstract: Gig work accessed through the medium of digital platforms has become an increasingly researched and debated topic owing to several features which distinguish it from other variants of temporary work. It represents a form of working that typically falls outside the standard boundaries of the organisation and employment relationships and where technology has a most pervasive role. This paper, alongside five special issue contributions, explores the enactment of technologically mediated HRM in the gig economy. We make the case for enhanced research efforts on HRM without employment contexts. More specifically, there is a need for greater appreciation of the diversity within the digital platform classification, and what this may mean for the role and value of HRM. While gig workers tend to fall outside the HRM field's remit, we expose how this is problematic given the presence of several activities and practices that one traditionally associates with the HR function.